Learners’ perceptions and experience of the content and teaching of sexuality education: Implications for teacher education - Dennis Francis, Dennis Francis; VILJOEN, MARIANNE (South African Journal of Higher Education, 2016)
This article aims to explore Grade 11 learners’ perceptions and experience of the teaching of sexuality education. A total of 270 adolescent boys (n 121) and girls (n 149) from the Heidedal suburb of the greater Mangaung Municipality, South Africa, completed an anonymously written Teaching of Sexuality Education Attitude Scale (TSEAS). The questionnaire was constructed on a six-point Likert scale with response options ranging from 1 (highly disagree) to 6 (highly agree). Factor analysis of the questionnaire and an independent sample t-test for determining the gender mean differences on scale dimensions were done. The findings show that boys were significantly more open and comfortable to speak about sex during class than girls. In addition, boys reported that they were more comfortable with their sex education teacher and that they, more than girls, could share their experiences about sex. In conclusion, learners’ perceptions and experience of the teaching and learning of sexuality education may be useful in scaling up efforts to enhance the content of sexuality education and how it is taught. More importantly, however, there is a need to find ways to increase the participation and comfort level of girls in the sexuality education classroom. We conclude our article with implications for teacher education. Keywords: sexuality education, teaching, gender, HIV/AIDS, South Africa